Management of steroid-resistant nephrotic syndrome in children and adolescents. (December 2018) - Tullus, Kjell; Webb, Hazel; Bagga, Arvind
Summary: More than 85% of children and adolescents (majority between 1–12 years old) with idiopathic nephrotic syndrome show complete remission of proteinuria following daily treatment with corticosteroids. Patients who do not show remission after 4 weeks' treatment with daily prednisolone are considered to have steroid-resistant nephrotic syndrome (SRNS). Renal histology in most patients shows presence of focal segmental glomerulosclerosis, minimal change disease, and (rarely) mesangioproliferative glomerulonephritis. A third of patients with SRNS show mutations in one of the key podocyte genes. The remaining cases of SRNS are probably caused by an undefined circulating factor. Treatment with calcineurin inhibitors (ciclosporin and tacrolimus) is the standard of care for patients with non-genetic SRNS, and approximately 70% of patients achieve a complete or partial remission and show satisfactory long-term outcome. Additional treatment with drugs that inhibit the renin–angiotensin axis is recommended for hypertension and for reducing remaining proteinuria. Patients with SRNS who do not respond to treatment with calcineurin inhibitors or other immunosuppressive drugs can show declining kidney function and are at risk for end-stage renal failure. Approximately a third of those who undergo renal transplantation show recurrent focal segmental glomerulosclerosis in the allograft and often respond to combined treatment with plasma exchange, rituximab, and intensified immunosuppression.